Integration of CW-MFC and anaerobic granular sludge to explore the intensified ammonification-nitrification-denitrification processes for nitrogen removal. (September 2021) - Zhu, Cong-Yun; Wang, Jun-Feng; Li, Qu-Sheng; Wang, Li-Li; Tang, Guan-Hui; Cui, Bao-Shan; Bai, Junhong
Abstract: The integration of constructed wetland-microbial fuel cell (CW-MFC) and anaerobic granular sludge (AGS) is an important way to promote its ammonification efficiency and decrease the land use scale. This study explored the integration of CW-MFC and AGS for nitrogen removal via the intensified ammonification-nitrification-denitrification processes with initial NH3 –N, NO3 –N, Org-N and total nitrogen (TN) concentrations of 10.5, 13.8, 21.4, and 45.7 mg L −1 in wastewater. Two reactors with AGS inoculated with a separated area (R1) and directly inoculated into gravel substrate (R2) were designed, respectively. Results showed that chemical oxygen demand (COD) removal efficiency could reach 85% in R1 and 81% in R2, and the conversion of Org-N to NH3 –N and NO3 –N to gaseous nitrogen were 80% and 90%, respectively. Although the conversion efficiency of NH3 –N to NO2 –N/NO3 –N via nitrification process was only 18%, it could reach 45%, 94%, and 98% with the aeration rates of 50-, 100-, and 200-mL min −1 . According to microstructural property and microbial community analyses, the separation gravel substrate and AGS areas in R1 availed for stable particle size of AGS, archaeal diversity, and metabolic activity even with a 1.5 times daily wastewater treatment capacity than that of R2. Overall, although the intensified ammonification-nitrification-denitrification processes for nitrogen removal could be achieved with supplementary aeration, further investigation is still needed to explore other substrate materials and high CW-MFC/AGS volume ratio for intensified nitrification process in CW-MFC associated with AGS. Graphical abstract: Image 1 Highlights: High-rate nitrogen removal AGS CW-MFC was developed with 38 g N m −2 d −1 loading rate. Ammonification in AGS CW-MFC reaches 80% with Org-N loading rate of 6–18 g N m −2 d −1 . Nitrification of AGS CW-MFC promotes by 76% with aeration rate of 100-mL min −1 . Denitrification in AGS CW-MFC reaches 90% via bio-metabolism and electrons transfer. Separated gravel and AGS areas in CW-MFC availed for AGS stability and metabolism.